APPLICATION OF THE MAGNETISM FOR GEOLOGICAL-GEOPHYSICAL TASKS - MENSHOV, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The possibility of using the soil magnetism for hydrocarbons prospecting, ecogeophysics and urbogeophysics investigations, in agriculture is considered. The distributions of the investigated magnetic parameters in Ukraine soils are described.